2004
DOI: 10.1590/s0101-81752004000300009
|View full text |Cite
|
Sign up to set email alerts
|

Nesting biology of Centris (Hemisiella) tarsata Smith (Hymenoptera, Apidae, Centridini)

Abstract: Nests of Centris tarsata Smith, 1874 were obtained from trap-nests in areas of dry semi-deciduous forest (Baixa Grande) and caatinga (Ipirá), in the State of Bahia. Nesting occurred in bamboo canes and in tubes of black cardboard with 5.8 cm (= small tube) and 10.5 cm (= large tube) in length and 0.6 and 0.8 cm in diameter, respectively. In both areas C. tarsata nested during the wet season producing four generations in Baixa Grande and three generations in Ipirá. The immatures of one generation underwent diap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
77
2
30

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 31 publications
8
77
2
30
Order By: Relevance
“…Fluctuations in annual frequencies of nesting, as occurred in this study, have also been reported by other authors (FRANKIE et al 1993, MORATO et al 1999, PEREIRA et al 1999, AGUIAR & GARÓFALO 2004 working with trap-nests. FRANKIE et al (1998) suggested that such fluctuations would be a regular characteristic of cavity-nesting bee species, and that different species would be affected differently by climatic changes between years.…”
Section: Nesting Seasonsupporting
confidence: 91%
See 3 more Smart Citations
“…Fluctuations in annual frequencies of nesting, as occurred in this study, have also been reported by other authors (FRANKIE et al 1993, MORATO et al 1999, PEREIRA et al 1999, AGUIAR & GARÓFALO 2004 working with trap-nests. FRANKIE et al (1998) suggested that such fluctuations would be a regular characteristic of cavity-nesting bee species, and that different species would be affected differently by climatic changes between years.…”
Section: Nesting Seasonsupporting
confidence: 91%
“…Although this species showed low nesting frequency in Baixa Grande, it was the second most abundant species at Guariba Biological Reserva (AGUIAR & MARTINS 2002). It is important to observe that while C. tarsata is a predominant species in some areas of the northeastern part of Brazil , AGUIAR 2002, AGUIAR & MARTINS 2002, AGUIAR & GARÓFALO 2004, C. analis is, usually, the most abundant Centris species in forest fragments of the southeastern part (CAMILLO et al 1995, GARÓFALO 2000.…”
Section: Species Richness and Abundancementioning
confidence: 99%
See 2 more Smart Citations
“…The tribe includes species that excavate simple or compound nests in fl at ground or in vertical banks (Vinson & Frankin 1988, Batra & Schuster 1977, Rozen & Buchmann 1990, Aguiar & Gaglianone 2003. Other species build their nests in holes of wood, such as tree trunks, inside termitaria or use preexisting cavities, such as cells abandoned by wasps or other bees (Coville et al 1983, Silva et al 2001, Aguiar et al 2006, Ramos et al 2007a, old beetle boring (Michener & Lange 1958) and trap-nests (Garófalo et al 1989, Pereira et al 1999, Aguiar & Garófalo 2004, Mendes & Rêgo 2007.These bees are considered effective pollinators for a variety of plant species, particularly "oil plants" such as Malpighiaceae, Krameriaceae and Scrophulariaceae (Vogel 1974, Neff & Simpson 1981, Buchmann 1987, Rêgo & Albuquerque 1989.Due to the essential ecological role played by these bees in a wide range of fl oral communities, studies of the biology of these species are important for conservational efforts to be developed for solitary bees and the plant species they pollinate. The aim of this study was to provide data on the nesting behavior of Centris vittata Lepeletier, a species distributed in several Brazilian ecosystems.…”
mentioning
confidence: 99%